The walking text : narrativised identities in the work of Philip Roth - Quinn, Leeanne (Trinity College (Dublin, Ireland). School of English, 2010)
The introduction to this thesis makes clear the need for a reconsideration of Roth's representation of self-identity through an examination of how selfhood and self identity are represented and experienced through narrative. The introduction defines several of the key terms through which this thesis operates and explains how its methodology privileges a reading of Roth that is character-orientated, taking its understanding of a character's narrativised experience from the theories of Paul John Eakin, whose theories of autobiography and self-identity are drawn upon where appropriate throughout the thesis.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.